Endovenous laser therapy for varicose vein (Medical Journal of Indonesia, 2013)
Laser has become a useful technology in treating venous incompetence especially superficial venous disease. Introduction of endovenous thermal ablation through endovenous laser therapy helped by duplex ultrasound guidance has provided an alternative for traditional saphenous vein stripping. High success rate, minor complications, and minimally invasive technique provide the advantages over traditional treatment. In this case illustrated, the endovenous laser therapy used for great saphenous varicose vein. Yet, future development in endovenous laser therapy is still needed and only long term follow-up and uniform reporting standards will provide the answers. (Med J Indones. 2013;22:117-20)